10 Years of the Palliative Medicine Working Group in the Network of Top Oncology Centers - Berendt, Julia; Gahr, Susanne; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-01-14

Early palliative care: current status of integration within German comprehensive cancer centers - Berendt, Julia; Stiel, Stephanie; Nauck, Friedemann; Ostgathe, Christoph (Supportive Care in Cancer, 2017)
The aim of this study is to describe how models of early integration (EI) of specialized palliative care (SPC) are applied to German comprehensive cancer center (CCCs).Heads of SPC departments of the 15 German CCCs were asked by email to describe the situation of early SPC in their CCC. The responses were analyzed using MAXQDA.Thirteen answers were allowed to be analyzed. Most of the department heads report that EI models of SPC are partially applied in the CCC (responses with "yes" or "partly," n = 10). Though they often describe that the models' implementation needs optimization and depends on temporary and financial restrictions or it has a pilot character. Models compromise structures like SPC unit, inpatient/outpatient SPC consultation team, and participation of members of SPC team in tumor boards. Moreover, other EI models of SPC quoted by the participants were standard operating procedures (SOP), screening tools, and information material for physicians, patients, and their related persons.Currently, German CCC models of EI of SPC are not applied in a standardized way. Approaches are still very diverse.
EVALuna2:26212

Erratum to: Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung im Erkrankungsverlauf (Die Onkologie, (2024), 30, 11, (1053-1061), 10.1007/s00761-024-01587-y) - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2025)
Im elektronischen Zusatzmaterial wurden ursprünglich falsche Dateien mit dem Artikel veröffentlicht. Sie wurden durch die richtigen Dateien ersetzt. Der Originalbeitrag wurde korrigiert.
CRIS-Team Scopus Importer:2025-04-25

Erratum to: SOP – Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung in der Sterbephase (Die Onkologie, (2024), 30, 10, (976-984), 10.1007/s00761-024-01585-0) - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2025)
Im elektronischen Zusatzmaterial wurden ursprünglich falsche Dateien mit dem Artikel veröffentlicht. Sie wurden durch die richtigen Dateien ersetzt. Der Originalbeitrag wurde korrigiert.
CRIS-Team Scopus Importer:2025-04-25

German measurements for family caregiver need assessment A narrative review on available self-assessments measuring different dimensions of family caregiver needs - Oubaid, Nikolas; Ullrich, Anneke; Schwenzitzki, Lisa; Berendt, Julia; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Pauli, Berenike; Simon, Steffen T.; Stiel, Stephanie; Van Oorschot, Birgitt; et al. (Onkologe, 2022)
Background Today, guideline-based care for patients with advanced cancer includes regular assessment of needs, not only for patients, but also for their family caregivers. Objectives Identification, evaluation and short description of German validated self-assessment instruments for needs assessment of family caregivers that can be used in daily practice. Materials and methods This narrative review is based on a syntax-based systematic literature search in PubMed (November 2021). Results The literature search identified 525 articles dealing with needs assessment for family caregivers. A multistep, criterion-referenced process identified 12 self-assessment instruments. These 12 capture (partly) the needs of family caregivers in terms of overall burden, psychosocial burden and psychopathological symptoms, quality of life, and support needs. They are available in German, validated, practicable in daily use, and easily accessible. The instruments-including their short versions-are presented with relevant information on use, target parameters, author references, availability, and evaluation. Conclusion This article can be helpful for practitioners wishing to implement a guideline-compliant, regular needs assessment of caregivers and to promote the provision of concrete support services. However, these instruments only cover individual aspects of possible needs of caregivers and it remains to be assessed how the 12 instruments can be combined for routine use or how a selection can be made.
CRIS-Team WoS Importer:2022-04-22

Integrating Palliative Care Into Comprehensive Cancer Centers: Consensus-Based Development of Best Practice Recommendations - Berendt, Julia; Stiel, Stephanie; Simon, Steffen T.; Schmitz, Andrea; Oorschot, Birgittvan; Stachura, Peter; Ostgathe, Christoph (Oncologist, 2016)
International associations admit that specialized palliative care (SPC) is an obvious component of excellent cancer care. Nevertheless, gaps in integration at the international level have been identified. Recommendations for integrating SPC in clinical care, research, and education are needed, which are subject of the present study.A Delphi study, with three written Delphi rounds, including a face-to-face-meeting with a multiprofessional expert panel (n = 52) working in SPC in 15 German Comprehensive Cancer Centers (CCCs) funded by the German Cancer Aid was initiated. Initial recommendations are built on evidence-based literature. Consensus was defined in advance with >=80% agreement based on the question of whether each recommendation was unambiguously formulated, relevant, and realizable for a CCC.A total of 38 experts (73.1%) from 15 CCCs performed all three Delphi rounds. Consensus was achieved for 29 of 30 recommendations. High agreement related to having an organizationally and spatially independent palliative care unit (>=6 beds), a mobile multiprofessional SPC team, and cooperation with community-based SPC. Until round 3, an ongoing discussion was registered on hospice volunteers, a chair of palliative care, education in SPC among staff in emergency departments, and integration of SPC in decision-making processes such as tumor boards or consultation hours. Integration of SPC in decision-making processes was not consented by a low-rated feasibility (76.3%) due to staff shortage.Recommendations should be considered when developing standards for cancer center of excellence in Germany. Definition and implementation of indicators of integration of SPC in CCCs and evaluation of its effectiveness are current and future challenges.General and specialized palliative care (SPC) is an integral part of comprehensive cancer care. However, significant diversity concerning the design of SPC in the German Comprehensive Cancer Center (CCC) Network led to the establishment of consensual best practice recommendations for integration of SPC into the clinical structures, processes, research, and education throughout the CCC network. The recommendations contribute to a greater awareness relating to the strategic direction and development of SPC in CCCs. The access to information about SPC and access to offers regarding SPC shall be facilitated by implementing the recommendations in the course of treatment of patients with cancer.
EVALuna2:26207

Integration of Palliative Care into the Comprehensive Cancer Center of Germany - Consultation Hours and Fellowship Rotations of the Specialized Palliative Care - Berendt, Julia; Thomas, Michael; Neukirchen, Martin; Schwartz, Jacqueline; Hense, Joerg; Tewes, Mitra (Deutsche Medizinische Wochenschrift, 2018)
BACKGROUND: Comprehensive Cancer Centers are characterized by interdisciplinary exchange for meeting increasingly complex care needs during the course of the disease. Tumor consultations hours and fellowship rotations build hereby bridges between the subjects and disciplines. OBJECTIVES: In order to be able to provide support in the Comprehensive Cancer Center Network for the further integration of specialized palliative medicine, it was highlighted to what extent consultation hours and fellowship rotations for the palliative care are integrated into the centers. METHODS: Information about the spS and fellowship rotation of the Comprehensive Cancer Center (n = 16), which had previously been funded by the Cancer Aid, was paper-based collected with a survey questionnaire. For this purpose, the heads of the palliative care departments of the centers were interviewed from July to August 2017. The evaluation was performed by SPSS (frequency, mean value, median, range). RESULTS: 15 from 16 centers responded to the survey (93.75 %). Nine centers (60 %) have a consultation hour for palliative care. Four from nine centers can submit this offer for ≥ 4 hours (44.4 %). Fellowship rotations in the palliative care occur primarily in all centers from oncology / hematology (n = 11, 73.3 %) and anaesthesia (n = 6) and often for a twelve months (n = 11) period of time. CONCLUSION: Outpatient structures of the palliative care have been insufficiently implemented to a consultation hour within Comprehensive Cancer Centers. The existing effort to integrate palliative care into the oncological course of disease requires further structuring in order to increase the visibility of palliative care services. Fellowship rotations in the palliative care department are regularly implemented in the network even if only for some of the subjects in order to raise awareness of the possibilities of the palliative care.
EVALuna2:34501

Integration von Palliativmedizin in onkologische Spitzenzentren Deutschlands - ambulante Sprechstunden und Rotationsprogramme der spezialisierten Palliativmedizin - Berendt, Julia; Thomas, Michael; Neukirchen, Martin; Schwartz, Jacqueline; Hense, Jörg; Tewes, Mitra (TumorDiagnostik & Therapie, 2019)
Background Comprehensive Cancer Centers are characterized by interdisciplinary exchange for meeting increasingly complex care needs during the course of the disease. Tumor consultations hours and fellowship rotations build hereby bridges between the subjects and disciplines. Objectives In order to be able to provide support in the Comprehensive Cancer Center Network for the further integration of specialized palliative medicine, it was highlighted to what extent consultation hours and fellowship rotations for the palliative care are integrated into the centers. Methods Information about the spS and fellowship rotation of the Comprehensive Cancer Center (n=16), which had previously been funded by the Cancer Aid, was paper-based collected with a survey questionnaire. For this purpose, the heads of the palliative care departments of the centers were interviewed from July to August 2017. The evaluation was performed by SPSS (frequency, mean value, median, range). Results 15 from 16 centers responded to the survey (93.75%). Nine centers (60%) have a consultation hour for palliative care. Four from nine centers can submit this offer for ≥4 hours (44.4%). Fellowship rotations in the palliative care occur primarily in all centers from oncology/hematology (n=11, 73.3%) and anaesthesia (n=6) and often for a twelve months (n=11) period of time. Conclusion Outpatient structures of the palliative care have been insufficiently implemented to a consultation hour within Comprehensive Cancer Centers. The existing effort to integrate palliative care into the oncological course of disease requires further structuring in order to increase the visibility of palliative care services. Fellowship rotations in the palliative care department are regularly implemented in the network even if only for some of the subjects in order to raise awareness of the possibilities of the palliative care.
CRIS-Team Scopus Importer:2019-06-21
Keywords: consultation; fellowships; outpatient clinics; palliative care

Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung im Erkrankungsverlauf - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2025-02-04

Palliativmedizin in onkologischen Spitzenzentren - Gahr, Susanne; Berendt, Julia; Tewes, Mitra (Forum, 2023)
Die bestmögliche Versorgung schwerstkranker und sterbender Patienten vom Zeitpunkt der Diagnosestellung bis zum Tod ist eine zentrale Aufgabe der Palliativversorgung onkologischer Zentren und Spitzenzentren. Die dynamische Entwicklung der Palliativmedizin in den letzten Jahren hat dabei zu einer sehr heterogenen Versorgungslandschaft mit unterschiedlichen Angeboten und Konzepten geführt. Vertreter der Arbeitsgruppe Palliativmedizin aus den durch die Deutsche Krebshilfe geförderten Comprehensive Cancer Centers (CCCs) haben für viele Bereiche der Patientenversorgung, Forschung und Lehre die Notwendigkeit erkannt, die Integration der Palliativmedizin in die etablierten Strukturen und klinischen Abläufe mit ihren gebündelten Kompetenzen zu intensivieren, innerhalb und außerhalb der CCCs. Aufgaben und Ziele der Arbeitsgruppe Palliativmedizin bestehen in der gemeinsamen Vernetzung, im fachlichen Austausch und in der Entwicklung gemeinsamer Standards sowie darin, die Erkenntnisse anderen onkologisch versorgenden Einrichtungen zur Verfügung zu stelle
Keywords: Onkologie; Palliativversorgung; Comprehensive Cancer Centers; Vernetzung; Behandlungsstandards

Scoping Reviews in Palliative Research - Heckel, Maria; Berendt, Julia; Gahr, Susanne; Kauzner, Saskia; Schleef, Tanja; Herbst, Franziska A. (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-12-16

SOP – Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung in der Sterbephase - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-10-25

Standard operating procedures (SOPs) for palliative care : Presence and relevance of palliative SOPs within the network of German Comprehensive Cancer Centers (CCCs) funded by the German Cancer Aid - Stachura, P.; Berendt, Julia; Stiel, Stephanie; Schuler, U. S.; Ostgathe, Christoph (Schmerz, 2017)
Standard operating procedures (SOPs) can contribute to the improvement of patient care.Survey the presence and relevance of SOPs for palliative care (PC) within the network of German Comprehensive Cancer Centers (CCCs) funded by the German Cancer Aid.In a descriptive survey, palliative care services within 15 CCCs funded by the German Cancer Aid were asked to rate availability and thematic relevance of (1) symptom-related, (2) clinical pathways and (3) measures- and processes-oriented SOPs using a structured questionnaire.Pain management SOPs were the most common (n =11; 73 %). The most thematic relevance showed SOPs dedicated to pain management, care in the last days of life and delirium and other neuro-psychiatric diseases (each n =13; 87 %), followed by bowel obstruction, dyspnoea, nausea and palliative sedation (each n =12; 80 %).There is a wide gap between availability and perceived relevance of palliative care SOPs within the network of German CCCs funded by the German Cancer Aid. It is obvious that there is a need for further development of relevant SOPs in palliative care.
EVALuna2:26210

State of integration of palliative care at Comprehensive Cancer Centers funded by German Cancer Aid - Berendt, Julia; Oechsle, K.; Thomas, M.; Van Oorschot, B.; Schmitz, A.; Radbruch, L.; Simon, S. T.; Gaertner, J.; Thuss-Patience, P.; Schuler, U. S.; Hense, J.; Gog, C.; et al. (Deutsche Medizinische Wochenschrift, 2016)
Similarities and differences of integration of palliative care in clinical care, research and education structures at German Comprehensive Cancer Centers (CCC) are not known in detail.Provide an overview of availability and the way of integration of specialized palliative care at CCCs funded by the German Cancer Aid (Deutsche Krebshilfe, DKH).We conducted structured interviews from May to August 2014 with heads of palliative care departments (personally or by telephone). The interviews included a quantitative and a qualitative part. Other stakeholders of CCCs were asked the questions of the qualitative part. We evaluated the qualitative data using the content analysis by Mayring and MAXQDA 11.0. SPSS 21.0 was used for quantitative analysis.26 interviews were realized in 13 CCCs with 14 sites, which received funding, by DKH till August 2014 (one CCC had two university hospitals). Of these, 12 sites had a palliative care unit (86 %), 11 sites had palliative care consulting services available (79 %). Participation of palliative care specialists in tumor boards is not provided in 3 institutions (21 %) and is often not feasible on regular basis in the other institutions, due to staffing shortage. In 7 sites (50 %) defined criteria to integrate palliative care into CCCs were available. In the last 5 years specialized palliative care of 4 sites received an invitation for a research project by another department within the CCC (29 %). 10 sites (71 %) had started own palliative care research projects. Chairs in palliative care were available in 4 CCCs (29 %).The extent and depth of palliative care integration in the 14 CCC sites is heterogeneous.
EVALuna2:26189

Symptom burden and relief in palliative care units of German Comprehensive Cancer Center and other hospitals - Berendt, Julia; Brunner, Sarah; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph; Gahr, Susanne (Journal of Cancer Research and Clinical Oncology, 2024)
Purpose: The National Hospice and Palliative Registry contains patient data from German hospice and palliative care facilities about symptoms. The aim of the study at hand is to differentiate symptom burden of patients in palliative care units between Comprehensive Cancer Center (CCC) and other hospitals regarding symptom burden and relief of patients in palliative care units. Methods: The registry analysis provided data of patients in palliative care units (2014–2018). We analyzed characteristic and symptom-related data on 18 symptoms, with considerable symptom-burdened patients (moderate or severe). We followed a cancer (yes/no) and facility-specific descriptive analysis (f, %, μ, Mdn, SD, V, r) using SPSS. Results: We evaluated 10,447 patient records (CCC: 4234 pts/non CCC 6,213 pts), 82% with a cancer diagnosis. For cancer patients, the mean age in CCC-affiliated palliative care units was 68 (SD 19–99) years, in others 73 (SD 23–104) years (p < 0.05; V = 0.2). The proportion of patients with significant symptom burden is lower in CCC-affiliated than in other palliative care units. The difference between facilities shows a significant weak effect in pain, vomiting and constipation, depressiveness, anxiety, and tension. The proportion of cases which symptom burden could be alleviated is higher in CCC-affiliated palliative care units with significant weak/medium effect in pain, nausea, vomiting, shortness of breath, constipation, wound care problems, depressiveness, anxiety, tension, confusion, and problems in organizing care. Conclusion: We found differences in symptom burden and symptom relief between CCC-affiliated and other palliative care units. CCCs should continue to feel responsible for sharing knowledge about symptom relief, such as through standard operating procedures and education.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Cancer; Palliative care; Registry; Symptom burden; Symptom relief

Versterben im Krankenhaus – Umgang mit und Versorgung von Verstorbenen und ihren An- und Zugehörigen - Kreymann, Frank; Ahn, Johann; Behzadi, Asita; Sibbe, Angela; Reinholz, Ulrike; Demir, Mesut; Jentschke, Elisabeth; Rosenbruch, Johannes; Ullrich, Anneke; Hach, Michaela; Nehls, Michael; Mecklenborg, Marion; et al. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-05-31

Zusammenarbeit von Intensivmedizin und Palliativmedizin: Eine Bestandsaufnahme an den deutschen onkologischen Spitzenzentren - Berendt, Julia; Ostgathe, Christoph; Simon, S. T.; Tewes, M.; Schlieper, D.; Schallenburger, M.; Meier, S.; Gahr, Susanne; Schwartz, J.; Neukirchen, M. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2020)
Background: For intensive care patients with limited life expectancy the integration of palliative care in intensive care may be beneficial. However, little is known about the extent of this interdisciplinary collaboration. Objectives: The support given by palliative medicine in German oncological centers and used by the intensive care units should be recorded. Material and methods: A descriptive survey was conducted in all of the 16 Comprehensive Cancer Centers (CCC) funded by German Cancer Aid. The questionnaires were sent to the head of department of the CCCsʼ specialized palliative care teams. Data were collected for the year 2016. Quantitative data were analysed to establish frequencies, given as mean and median. A qualitative section asked for trigger factors, i.e., patient characteristics triggering a palliative care consultation. Evaluation was inductively carried out by content analysis according to Mayring. Results: Data from 15 of the 16 CCCs (94%) were obtained between July and August 2017. In 2016, the median of intensive care patients with palliative care consultations was 33 (minimum 0, maximum 100). The median of nine patients were transferred from an intensive care unit to a palliative care unit (minimum 1, maximum 30). Multidisciplinary ward rounds by both intensive and palliative care staff were available in two CCCs on a regular basis. Two CCCs implemented screening tools to integrate specialized palliative care into intensive care. From 23 responses concerning triggers, three categories were established, i.e., “team’s decision and attitude”, “patient’s condition” and “desires of patients and relatives”. Conclusions: Palliative care is available in German CCCs. However, the degree of integration of specialized palliative care into intensive care units is low. Screening tools are available to identify patients with complex needs and to trigger a palliative care consultation. These tools, as well as joint ward rounds of intensive and palliative care staff, can improve the quality of patient centred care.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Intensive care patient; Interdisciplinary collaboration; Palliative care consultation service; Therapeutic goal setting; Trigger factors